Evaluation of transverse cerebellar diameter to abdominal circumference ratio in prediction of intrauterine growth retardation - Mourya, Saroj; Mourya, Harish K.; Makwana, Mohan; Gahlot, Hanslata; Verma, Suresh; Sharma, Seema (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: Intrauterine growth restriction accounts for a significant increase in perinatal mortality rate as well as immediate neonatal morbidity and continuing long term disability in some of the survivors. A different clinical problem develops in infants of same weight but different gestational age therefore identification of high risk newborns based on gestational age and weight. Hence without an accurate knowledge of gestational age, the clinician is significant hampered in an attempt to differentiate truly growth restricted fetus from a patient with incorrect gestational parameters. TCD is emerging as a new sonografic parameter and least affected by fetal growth restriction while liver is most affected organ. Methods: The patients were sonographically examined for TCD/AC ratio. The best cut-off value of TCD/AC ratio in predicting IUGR was determined by a receiver operating characteristic (ROC) curve. The fetus with a TCD/AC ratio greater than the cut-off value would be antenatally diagnosed as IUGR for every gestational week. Standard definition of IUGR was a low birth weight, less than the 10th percentile. Results: Eighty pregnancies with suspected IUGR were analyzed. The prevalence of IUGR among the study group was 51.5%. The best cut-off value of the TCD/AC ratio for predicting IUGR was 15.87%, giving the sensitivity, specificity, positive predictive value and negative predictive value of 81.25%, 62.25%, 89.65%, and 45.45%, respectively. Conclusions: The sonographic fetal TCD/AC ratio as a gestational age-independent, useful, feasible and sensitive method for antenatal diagnosis of IUGR, especially in pregnancy with uncertain gestational age. Routine TCD/AC ratio should be performed to diagnose IUGR.